Peri-implant Tissues and Diseases - YILDIRIM, HATİCE SELİN; KURU, LEYLA; AĞRALI, ÖMER BİRKAN (MARMARA UNIV, INST HEALTH SCIENCES, 2017)
Peri-implant diseases occur due to imbalance between host response and biofilm after successful osseointegration of an implant with the bone. Among peri-implant diseases, peri-implant mucositis is used to describe the presence of inflammation only within the mucosa, whereas peri-implantitis is characterized by loss of supporting bone in addition to the inflammation within the mucosa. For the diagnosis of peri-implant diseases, probing depth, bleeding on probing, and suppuration are clinically assessed. Additionally, supporting bone levels are radiographically evaluated. Smoking, lack of oral hygiene, history of periodontal disease, diabetes mellitus, cardiovascular diseases, and implant surface characteristics are the known risk factors for the development of peri-implant diseases. For the treatment of peri-implant mucositis, antimicrobial treatment is performed together with mechanical debridement. However, these treatment approaches are not sufficient for peri-implantitis cases. For the treatment of peri-implantitis, resective and/or regenerative surgical interventions are used in addition to mechanical debridement. It is crucial to improve the knowledge among dentists about the prevention and progression of peri-implant diseases. On the other hand, patients should be advised regular dental visits and to maintain the highest level of oral hygiene.
Keywords: Peri-implant mucositis; peri-implantitis; peri-implant risk factors; peri-implant treatment; EUROPEAN WORKSHOP; CONSENSUS REPORT; PREVALENCE; MUCOSITIS; BONE; THERAPY; COLONIZATION; DELIVERY; SURGERY; SYSTEMS